Effect of Self-Focusing on Propagation of a Laser Beam in the Atmosphere Along a Slant Path - Liyun Pu; Xiaoqing Li; Xiaoling Ji (IEEE Photonics Journal, 2023)
The equivalent B-integral phase screen (EBPS) method of numerical simulation is proposed to study the propagation of a high-power laser beam in the atmosphere along a slant path, and the computational accuracy and efficiency of the EBPS method are confirmed. It is shown that a decrease of the self-focusing caused by the atmosphere refraction effect. However, the refraction correction for the elevation angle is hardly affected by the self-focusing effect. On the other hand, the analytical expressions of the B integral and the optimal initial beam power of a high-power laser beam propagating in the atmosphere along a slant path are derived. It is found that the optimal beam power and the target maximum intensity decrease as the apparent elevation angle decreases, while the optimal beam power decreases but the target maximum intensity increases as the wavelength decreases. A method to optimize the beam quality on the target is presented.